New species of lichenicolous fungi from the Canary Islands - Pérez-Vargas, Israel; Etayo, Javier; Hernández-Padrón, C. (Phytotaxa, 2013)
Three new species of lichenicolous fungi from the Canary Islands (Leightoniomyces canariensis, Lichenodiplis anomalus and Perigrapha phaeophysciae), are described as new to science. A description of each species is given together with notes on their chemistry, distribution, ecology and taxonomy. Similar species are briefly discussed.